WORK WITH PROTECTED DATA - HAMBALÍK, Alexander (Trends in education, 2012)
This submission contains basic information about working with protected data. It describes the application (Manager), which was developed at the author's workplace. This application facilitates more effective work in small and medium-sized businesses or educational establishments. It allows users to map possible data sources, monitor the creation, processing and disposal of protected data as required by law.
Keywords: protected and sensitive data; data protection law; work with protected data.